DEVELOPMENT OF EDUCATION DISTRICTS IN THE STATE SYSTEM OF RUSSIA: HISTORY AND MODERNITY (Revista Inclusiones, 2020)
Education, being an important resource of social, political and economic development of the country, helps preserve and reproduce ethnic, social and cultural values at a new level, thus fostering the building of civic society. The relevance of creating education districts lies in the necessity to build a unified countrywide education space. The methodological foundation of the paper rests on a complex of research methods and approaches – systemic, axiological and cultural, as well as the following methods: historical retrospective and comparative analysis of education systems, which makes it possible to build logical schemes; on praxymetric method, and on modeling the processes of social and pedagogical character. The authors present a historical overview of the emergence and development of ‘education district’ as a social phenomenon and consider its role in building a unified education space in the country.